Exploring the binding pattern between pepsin and deferasirox using detailed experimental and computer simulation methods. Issue 65 (5th November 2018) - Yang, Ji; Du, Qiaohong; Gan, Na; Chen, Yongkuan; Yang, Liu; Liu, Zhihua; Zhao, Hui; Sun, Qiaomei; Li, Hui
Abstract : Investigation on the binding properties of deferasirox to pepsin. Abstract : Steady-state fluorescence spectroscopy indicated that a ground state complex was formed between deferasirox (DFX) and pepsin. The binding parameters and thermodynamic parameters of pepsin–DFX complex formation suggested the presence of only one high affinity binding site in the binding process of DFX and pepsin and that the binding process was hydrogen bond dominated. According to the MD simulation optimal pepsin–DFX binding model analysis, the binding force between DFX and pepsin was mainly hydrogen bonding, and the hydrophobic interaction was supplemented. Synchronous fluorescence spectroscopy and 3D fluorescence spectroscopy indicated that the binding of DFX to pepsin had minor effect on the protein structure and function. Circular dichroism spectra showed that DFX had no significant effect on the main secondary structure of pepsin. MD analysis also showed that DFX did not affect the looseness of pepsin and the overall secondary structure, but it affected the amino acid residue sequence Leu48-Ala49-Cys50-Ser51-Asp52. Pepsin enzyme activity test showed that the addition of DFX had a slight enhancement effect on the activity of pepsin. Combined with the MD results, DFX bound to pepsin and was closer to the pepsin active site Asp-215, which may affect the electrical environment of Asp-215 residues and enhance the activity of pepsin.